Analyzing the falling solar and wind tariffs: Evidence from India - Kanika Chawla; Manu Aggarwal; Arjun Dutt (Asian Development Bank Institute (ADBI), 2020)
India needs to considerably accelerate its solar and wind energy capacity addition in order to meet its renewable energy (RE) capacity deployment targets. Besides policy commitments, the cost-competitiveness of RE tariffs is a major determinant of capacity addition. This paper focuses on the major determinants of RE tariffs, disaggregating the impact of equipment-related factors and financing costs (costs of debt and equity). The paper finds that financing costs account for the largest component - over 50% of RE tariffs. Further, equipment-related factors have been the major drivers of tariff reduction historically, accounting for 73% of the solar tariff reduction between January 2016 and May 2017. However, the paper demonstrates that there could be a role reversal - changes in financing costs could drive future decreases in both solar and wind tariffs. This necessitates the de-risking of these sectors through suitable policy- and market-led interventions in order to lower financing costs.
Keywords: Q20; Q27; 330; renewable energy; solar and wind tariffs; India